Extreme heat loss in the Northern Red Sea and associated atmospheric forcing - Papadopoulos, Vassilis P.; Krokos, George; Dasari, Hari Prasad; Abualnaja, Yasser; Hoteit, Ibrahim (Frontiers in Marine Science, 2022)
A regional, high-resolution reanalysis was analyzed to explore extreme heat loss events in the Northern Red Sea (NRS) and their links to specific regional atmospheric circulation patterns. Such events are determinant for the overturning circulation of the Red Sea and occur frequently between November and March, with maximum frequency during December and January. During these events, the most intense heat loss, often with daily-averaged values lower than -1000 W/m2, is found over the southern half of the Gulf of Aqaba and along the western coastline of the open NRS. Analyses of the spatial modes of variability of these events suggest that the majority of them extend over the entire NRS in an almost uniform way; however, secondary, nonuniform patterns related to regional adjustment in the wind field are also identified. The uniform cold outbursts are associated with distinct atmospheric circulation patterns, which favor the transfer of cold air masses from higher latitudes over the eastern Mediterranean Sea via a strong northwest wind field. Nonuniform events affect considerable parts of the NRS and occur when cold and dry air masses reach the NRS through the Middle East and the northern part of the Arabian Peninsula. The regional sea level pressure drives a clockwise rotation of the wind field that ultimately blows from the northeast/east direction. This rotation of the wind field favors local intensification and lee areas defined by the complex topography and characteristic gaps in the mountain chain along the eastern coastline of the NRS, reflecting the differentiations in the spatial distribution of the heat flux minima.